The use of some therapeutic alternatives in inhibiting the growth of bacteria Proteus mirabilis that causes urinary tract infections (Journal of the College of Basic Education, 2022)
The study included the current test effectiveness of natural extracts water and alcohol, vinegar, juice and vegetable oil of Mentha piperita (mint) and compare their effectiveness with some probiotic therapeutic such as lactic acid bacteria and yeast Saccharomyces boulardii to assess their ability to inhibit the growth of bacteria Proteus mirabilis isolated from urinary tract infections using agar diffusion method. The results showed that the extract, vinegar and vinegar alone and extracts alcoholic were more effective in inhibiting the growth of bacteria from water extracts juice and vegetable oil mint , and recorded the highest rate of inhibition of 29 mm , 26 mm , 24 mm respectively, compared to an average diameters inhibition of lactic acid bacteria and yeast S. boulardii as it recorded the highest area of ​​inhibition of 6 mm and 3 mm respectively , which are less effective for the inhibition rate diameters bacteria using plant extracts.